2007
DOI: 10.1152/jn.00128.2007
|View full text |Cite
|
Sign up to set email alerts
|

HVC Neural Sleep Activity Increases With Development and Parallels Nightly Changes in Song Behavior

Abstract: Crandall SR, Adam M, Kinnischtzke AK, Nick TA. HVC neural sleep activity increases with development and parallels nightly changes in song behavior. J Neurophysiol 98: 232-240, 2007. First published April 11, 2007 doi:10.1152/jn.00128.2007. Sleep abnormalities are coexpressed with human communication disorders. Recent data from the birdsong system, the best model for human speech, indicate that sleep has a critical role in vocal learning. To understand the neural mechanisms that underlie behavioral changes dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Similarly, it was found that tutor-song-specific neuronal bursting activity in RA of sleeping juvenile zebra finches preceded the changes in singing observed the next day and was dependent on normal sensorimotor feedback (Shank & Margoliash 2009). Alternatively, the correlation between Zenk expression and strength of song learning in the NCM might be indicative of changes in general patterns of nocturnal brain activity related to the developmental process, such as that shown in the song system (Crandall et al 2007;Shank & Margoliash 2009). Taken together, these different findings suggest that sleep is important for sensorimotor learning of the BOS and auditory memory of the tutor song.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was found that tutor-song-specific neuronal bursting activity in RA of sleeping juvenile zebra finches preceded the changes in singing observed the next day and was dependent on normal sensorimotor feedback (Shank & Margoliash 2009). Alternatively, the correlation between Zenk expression and strength of song learning in the NCM might be indicative of changes in general patterns of nocturnal brain activity related to the developmental process, such as that shown in the song system (Crandall et al 2007;Shank & Margoliash 2009). Taken together, these different findings suggest that sleep is important for sensorimotor learning of the BOS and auditory memory of the tutor song.…”
Section: Discussionmentioning
confidence: 99%
“…During the sensitive period for vocal learning in the wake state, a neural signal that is selective for the tutor song has been recorded in HVC (Nick and Konishi 2005b), which suggests that instructive auditory signals have access to the juvenile HVC during waking and, perhaps, during singing. In addition, HVC activity during sleep is positively correlated with overnight song stability in juveniles (Crandall et al 2007a), which suggests that HVC sleep activity may have a role in song learning. Collectively, these data indicate that HVC activity is dynamically regulated during song learning and suggest that it is a locus of vocal plasticity.…”
Section: Introductionmentioning
confidence: 92%
“…Combining antidromic stimulation with tetrode recording enables analysis of spike-time relationships among projection neurons and their local circuits. A defining characteristic of song system activity is its bursts of population activity that involve multiple neurons (Crandall et al 2007;Day et al 2009;Schmidt and Konishi 1998;Shank and Margoliash 2009). However, the types of HVC neurons that are coactive in the bursts have not been determined.…”
Section: Resultsmentioning
confidence: 99%